Metabolomics and 16S rRNA Gene Sequencing Analyses of Changes in the Intestinal Flora and Biomarkers Induced by Gastrodia-Uncaria Treatment in a Rat Model of Chronic Migraine - Wen, Zhiqi; He, Mingzhen; Peng, Chunyan; Rao, Yifei; Li, Junmao; Li, Zhifeng; Du, Lijun; Li, Yan; Zhou, Maofu; Hui, Ouyang; Feng, Yulin; Yang, Shilin (Frontiers in Pharmacology, 2019)
Accumulating evidence suggests that natural medicines have notable curative effects on neurological conditions, such as migraine, that are mediated by regulating the gut microbial flora. As a natural medicine pair from traditional Chinese medicine, Gastrodia and Uncaria (GU), have shown excellent efficacy in treating migraine, yet the role of gut microbes in the therapeutic efficacy of GU in chronic migraine (CMG) is unknown. Here, we performed a 16S rRNA gene sequencing and metabolomics study of the effects of GU in a nitroglycerin (NTG)-induced rat model of CMG. Our results showed that the gut microbial community structure changed significantly and was similar to that of control rats after GU administration in CMG rats. Specifically, GU increased the relative abundance of Bacteroides and Coprococcus and reduced the abundance of Prevotella_1 and Escherichia-Shigella in CMG rats, Metabolomics profiles of plasma and ileum contents of CMG rats using the ultra-performance liquid chromatography-mass spectrometer (UPLC-MS) revealed similar biomarkers in both samples, and GU treatment reduced 3-indoxyl sulfate, glutamic acid, L-tyrosine and L-arginine levels, and increased 5-HIAA, L-tryptophan and linoleic acid levels in plasma. Correlation analysis showed that the affected bacteria were closely related to amino acid metabolism. And most importantly, GU treatment hardly affected biomarkers in feces samples after inhibiting the activity of gut microbes. Collectively, these findings indicate that structural changes in gut flora are closely related to host metabolism, and regulating the gut microbial community structure and function may be of the importance in the mechanism underlying the therapeutic effects of GU in migraine.